Development of the block diagram of aircraft control system in case of an emergency - Казак, Василий Николаевич; Шевчук, Дмитрий Олегович; Васильев, Михаил Андреевич (Eastern-European Journal of Enterprise Technologies, 2014)
The main causes of an in-flight emergency were analyzed. Statistics of air accidents, caused by bird strikes were examined, an increase in such air accidents was noted. The formulas of the aerodynamic coefficients, which included emergency coefficients were developed. These formulas are systems of differential equations of the aircraft longitudinal and lateral movement, which include coefficients that describe the impact of an emergency on the aircraft aerodynamic properties. Equations of the aircraft motion dynamics taking into account the impact of an emergency were also formulated. The development of these equations is needed to create an aircraft control system in case of an emergency and work out a stabilizing effect. Block diagram of the aircraft flight control reconfiguration system in case of an emergency was elaborated. Designing the flight control reconfiguration system will allow to prevent emergency development and follow the intended flight path. As a result of the study, the basic causes of the failures that lead to emergencies, including lightning strike damage, bird strike damage, drive power loss or sensor failures were revealed. Necessary characteristics, determination of which allows to use model predictive control were also singled out. These characteristics are forecast horizon length, constraints on the control signal, sampling increment. Using the reconfiguration system will allow to reduce the accident risk, improve the aircraft sustainability and controllability, increase overall flight safety.